Cytogenetic and DNA barcoding reveals high divergence within the trahira, Hoplias malabaricus (Characiformes: Erythrinidae) from the lower Amazon River - Marques,Diego Ferreira (2013)
Molecular and cytogenetic data have provided evidence of cryptic speciation in the widespread South American trahira, Hoplias malabaricus. In the present study, karyotypes and DNA barcode sequences of specimens from seven populations inhabiting the lower Amazon River were analyzed in order to characterize the levels of genetic divergence within a single karyomorph. All the specimens presented karyotypes with 2n = 40 chromosomes (20m+20sm) that were consistent with the species' C karyomorph. The DNA barcodes revealed six haplogroups, with clear divergence between populations from Brazil and Argentina. The results support the species complex hypothesis and indicate that a single karyomorph of H. malabaricus may harbor more than one species